Use of Social Networks and their Impact on the Academic Performance of University Students in the Highlands of Peru - Casa-Coila, Manuela Daishy (Migration Letters, 2023)
The objective was to determine the relationship between the use of social networks and the impact on academic performance in students of the Professional School of Secondary Education (EPES), Faculty of Education Sciences (FCEDUC) of the National University of the Altiplano (UNA) Puno. The methodology follows the positivist paradigm, with a quantitative, non-experimental approach, with a cross-sectional correlational design. The population was 622 students and the sample was 259 students, selected by probability sampling. The survey and documentary analysis were applied and the instruments used were the questionnaire and the report card. The Kolmogorov-Smirnova normality test was performed, where p =.000 being nonparametric data. The result was according to rs = -.056; placing it in a very weak positive correlation. The conclusion is that the use of social networks has an impact on the academic performance of university students, and that the networks should be used appropriately.